ASSESSMENT OF THE EXTENT OF POST-HARVEST LOSSES ALONG THE CASSAVA VALUE CHAIN IN ANAMBRA STATE - Johnson Chimaobi, Chiekezie,; Njideka Rita, Chiekezie,; Eucharia C, Nwankwo,; Maurice U., Ozor, (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2023)
Addressing food security challenges is vital to the future of Africans and Nigerians. Despite the economic importance of cassava to the teaming populace in Nigeria, it is not devoid of post-harvest losses. This study explored the extent of post-harvest losses along the cassava value chain in Anambra State. The study adopted a descriptive survey design and was conducted in Anambra State in the South-Eastern part of Nigeria. The study population comprises all cassava farmers in the state's four Agricultural Zones (AZs): Onitsha, Aguata, Awka, and Anambra. Multistage, purposive, and random sampling techniques will be used to select the respondents for the study. Primary data was used for the study and collected using a well-structured questionnaire. Data collected was analyzed using descriptive statistics, Shannon's diversity index, and the Tobit regression model based on the study's objectives. The study revealed that the size of cassava postharvest loss is 266,116 kg. The chain of highest loss is at harvesting, which accounts for about 55 % of the total loss, followed by the loss at processing, 33 %, and then a loss at distribution, 12 %. The Tobit regression result of the factors responsible for cassava post-harvest loss shows that poor processing skills, farmers' well-being, poor planning, and pest and disease attacks are the significant factors determining cassava post-harvest loss in the study area. The study, therefore, recommends that policies be implemented to help the farmers reduce the losses, especially by enforcing adequate training of local farmers in cassava processing.